Evolution of the Anthropogenic Gallium Cycle in China From 2005 to 2020 - Jia, Hongxiang; Zhou, Yanjing; Wang, Anjian; Wang, Gaoshang; Li, Tianjiao; Wang, Chunhui; Xing, Wanli; Ma, Zhe; Li, Pengyuan (Frontiers in Energy Research, 2022)
Gallium is deemed to be a critical mineral given its irreplaceable use in consumer electronics and clean energy technologies. China has become a significant consumer of gallium while also playing a leading role in global gallium production, accounting for more than 90% of the world's primary output in recent years. However, the quantification and evolution of China’s gallium cycle is limited until now. This study aims to uncover the dynamic flows and stocks of gallium in China during the period of 2005-2020. The results reveal that: (1) From 2005 to 2020, China’s gallium demand increased more than 20-fold, as a result of the booming semiconductor industry and the surging use of gallium in some low-carbon technologies; (2) despite the inefficient recovery issues existed in the production stage, the supply of gallium extracted as a byproduct grew in tandem with the capacity of alumina production, resulting in a significant supply surplus of 948 t by 2020; (3) China exported nearly half of its gallium mainly as raw materials and final products, but still experienced a high reliance on imported gallium-containing intermediate products from abroad, such as integrated circuits; (4) the generations of in-use stocks and end-of-life flows of gallium have accelerated since 2005 and reached about 278 t and 169 t in 2020, respectively. These indicate a large amount of available secondary gallium resource, with nonexistent recycling. The results provide a basis for identifying gallium extraction, use, loss and recycling within its anthropogenic cycle in China, as well as guidance for stakeholders to make future decisions concerning ways to improve resource efficiency and promote sustainable gallium practices from a dynamic material cycle perspective.